PENGARUH PEMERIKSAAN PAJAK, PENAGIHAN PAJAK DAN KEPATUHAN WAJIB PAJAK TERHADAP EFEKTIFITAS PENERIMAAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA DEPOK CIMANGGIS - Zihan Ayu Safinatunnayah (Jurnal Bina Akuntansi, 2023)
The purpose of this study is to study the effect of tax audit, tax collection and taxpayer compliance toward tax revenue in Pratama Tax Service Office Depok Cimanggis in the period 2016-2019. This study uses an explanation method. The study population in this study were all taxpayers registered at the Depok Cimanggis Primary Tax Office. The sampling technique used was convenience sampling with 48 (forty eight) samples of monthly tax reports selected. The data collection technique in this study used document review, namely data collection was carriedout by examining the monthly tax reports at the Depok Cimanggis Primary Tax Service Office. The test results show that tax audit has a positive and significant effect on tax revenue, tax collection has a negative and insignificant effect on tax revenue, taxpayer compliance has no effect on tax revenue. Variable tax audit, tax collection and taxpayer compliance simultaneously have a positive and significant effect on tax revenue.